Pengaruh Pengawasan Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Perwakilan Badan Kependudukan Dan Keluarga Berencana Nasional Provinsi Maluku Utara - Kurshin M.S Marsaoly; Nurlaila Nurlaila (Jurnal Manajemen Sinergi, 2016)
This study aims to determine the effect fariabel supervision (X1) and discipline (X2) of the employee performance variables (Y). From the results of analysis calculation regresei multiple, results of hypothesis testing the effect of variable oversight of the variable performance of employees partially or individual, it can be concluded that the variable control positive and significant effect on employee performance and discipline partially positive and significant impact on the performance of employees in the representative body of the population and national family planning north Maluku province. The test results simultaneously monitoring variables and with the same work discipline has a positive and significant influence on employee performance variables representatives of the national population and family planning North Maluku Province. The test results influence the supervision and discipline of the employee performance, seen from the regression coefficient indicates that the work discipline (X2) provides the greatest influence on the performance of employees in the representative body of national population and family planning North Maluku Province.